2019
DOI: 10.1186/s12913-019-4842-2
|View full text |Cite
|
Sign up to set email alerts
|

Predicting patterns of service utilization within children’s mental health agencies

Abstract: BackgroundSome children with mental health (MH) problems have been found to receive ongoing care, either continuously or episodically. We sought to replicate patterns of MH service use over extended time periods, and test predictors of these patterns.MethodsLatent class analyses were applied to 4 years of visit data from five MH agencies and nearly 6000 children, 4- to 13-years-old at their first visit.ResultsFive patterns of service use were identified, replicating previous findings. Overall, 14% of cases had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
22
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 87 publications
2
22
3
Order By: Relevance
“…More than a third of referrals to CAMHS were re-referrals. This is comparable to previous findings from the UK [ 20 ] and Canada [ 38 , 39 ]. Despite high re-referral rates, there is a paucity of research on predicters of re-referral to outpatient CAMHS [ 40 ].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More than a third of referrals to CAMHS were re-referrals. This is comparable to previous findings from the UK [ 20 ] and Canada [ 38 , 39 ]. Despite high re-referral rates, there is a paucity of research on predicters of re-referral to outpatient CAMHS [ 40 ].…”
Section: Discussionsupporting
confidence: 91%
“…There is a need for more research on predictors of re-referral to outpatient CAMHS to identify targets for improvement of service provision for CYP with mental disorders. Regardless of the explanation, the high referral rates call for research on how to optimize services for children with a repeated need for referral to CAMHS [ 39 ]. With the knowledge of high comorbidity rates, it is positive that we found that previously having been assessed for a psychiatric diagnosis is associated with a decreased risk for a referral being rejected.…”
Section: Discussionmentioning
confidence: 99%
“…Peer relationship problems, as well as low frequency problems, such as substance abuse, sometimes coexist with complexity factors such as learning difficulties and family relationship difficulties (Cantwell & Baker, 1991;Denton & Kampfe, 1994) further identifying additional barriers to accessing care. Previous research has demonstrated that young people with fewer difficulties and contextual issues specific to impact on the family burden, child impairment and externalising difficulties were more likely to require minimal input (Reid et al, 2019). This raises further questions about service utility and barriers to care.…”
Section: Discussionmentioning
confidence: 98%
“…Further, with the high proportion of young people previously demonstrated as attending for a single session only (Wolpert et al, 2015), it is important to understand the specific needs of this group. This is particularly important in light of the prior research which highlights differential access to services amongst families (Pandiani et al, 2005;Reardon et al, 2017;Sadler et al, 2017;Stein et al, 2003) and differences between single session attenders both between and within services (Martin et al, 2017;Reid et al, 2019). Given the paucity of research in this specific area, the present research is key to contribute towards beginning to understand who these young people are, which in turn will allow further consideration to be given to how to best support them and their families, and the associated resource allocation in models such as THRIVE.…”
mentioning
confidence: 99%
See 1 more Smart Citation